Pengaruh Sistem Informasi Akuntansi Manajemen terhadap Kinerja Manajerial di Moderasi oleh Ketidakpastian Lingkungan pada PT Perkebunan Nusantara IV (Persero) Medan - Aulia Rahman Siregar; Irfan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to test and analyze the management accounting information system for managerial performance moderated by environmental uncertainty at PT Perkebunan Nusantara IV (Persero) Medan directly and indirectly. The approach used in this research is a causal approach. The population in this study was all employees of PT Perkebunan Nusantara IV (Persero) Medan. The sample in this study used the Slovin formula so that there were 80 employees of PT Perkebunan Nusantara IV (Persero) Medan. Data collection techniques in this research used documentation, observation and questionnaire techniques. The data analysis technique in this research uses a quantitative approach using statistical analysis using Auter Model Analysis, Inner Model Analysis and Hypothesis Testing. Data processing in this research uses the PLS (Partial Least Square) software program. The results of this research prove that the accounting information system directly influences managerial performance. Indirectly, environmental uncertainty cannot moderate the influence of management accounting information systems on managerial performance